Effects of vitamin E and selenium on performance, digestibility of nutrients, and carcass characteristics of Japanese quails reared under heat stress (34 °C) - Şahin, Kazım; Küçük, Ömer (Wiley, 2001)
This study was conducted to determine the effects of vitamin E (dL-alpha -Tocopheryl acetate) and selenium (Se; Na-2-SeO3) on performance, digestibility of nutrients and carcass characteristics of Japanese quails reared under chronic heat stress (34 degreesC). A total of 120 10-day-old Japanese quails were randomly assigned to four treatment groups, three replicates of 10 birds each. The birds with a 2 x 2 factorial design received either two levels of vitamin E (125 and 250 mg/kg of diet) or two levels of Se (0.1 or 0.2 mg/kg of diet). A 250-mg vitamin E/kg of diet compared with that of 125 mg/kg of diet and higher dietary Se inclusions (0.1 vs. 0.2 mg/kg) resulted in a better performance (p = 0.001). The interaction between vitamin E and Se for feed intake (p = 0.03), final body weight change (p = 0.03) and feed efficiency (p 0.001) was detected. Carcass yield increased with increasing both dietary vitamin E and Se (p = 0.001). The interactions on carcass characteristics were all non-significant (p > 0.06). Digestibility of nutrients (DM, OM, CP and ether extract) was higher with higher dietary vitamin E (p = 0.03), and DM digestibility was also higher with higher dietary Se (p = 0.05). There were no interactions detected for digestibility of nutrients (p = 0.28). From the results of the present study, it was concluded that a combination of 250 mg of vitamin E and 0.2 mg of Se provides the greatest performance in Japanese quails reared under heat stress and this combination can be considered as a protective management practice in Japanese quail diets, reducing the negative effects of heat stress.
Keywords: Egg-Production; Laying Hens; Temperature; Growth